Kebijakan Dan Praktek Kemitraan Era Orde Baru Serta Rekonstruksi Kebijakan Era Reformasi Di Indonesia - Yanto Sufriadi (Jurnal Hukum IUS QUIA IUSTUM, 2022)
This study focuses on the partnership policies and practices in the investment in plantation sub-sector in New Order Era and the reconstruction of reform policies in Indonesia. This study aims to explain partnership policies and practices in the investment in New Order Era in Indonesia, and the reconstruction of the Reform Era partnership policies. This research was conducted by using empirical legal research methods with a case study approach. Primary data was obtained from interviews with Plasma Farmers in the Plantation Sub-sector in Bengkulu, and secondary data was obtained from literature studies sourced from books, journals and laws and regulations. This study concludes that: (1). The New Order Partnership Policy in Indonesia was not intended to implement the principle of joint effort in Article 33 of the 1945 Constitution, but in the context of implementing the World Bank and IMF projects since 1976, which were later established as investment policies in 1995; (2). The practice of the Nuclear-Plasma partnership in the Plantation Sub-sector during the New Order placed Plasma companies under the Subordination of the Core Company and lacked protection from the Government, resulting in an exploitative pattern of economic relations; and (3). Reconstruction of the Reform Era's Partnership Policy is carried out by providing ease of business licensing, legal protection, and empowerment of Cooperatives, Micro Enterprises, and Small Businesses, as well as continuous monitoring of partnerships.Key Words : Exploitative; the new order Era; reform era; partnership policy; investmentAbstrakKajian ini berfokus pada kebijakan dan praktik kemitraan dalam investasi subsektor perkebunan di Era Orde Baru dan rekonstruksi kebijakan Era Reformasi di Indonesia. Penelitian ini bertujuan untuk menjelaskan kebijakan dan praktik kemitraan dalam investasi Era Orde Baru di Indonesia, dan rekonstruksi kebijakan kemitraan Era Reformasi. Penelitian ini dilakukan menggunakan metode penelitian hukum empiris dengan pendekatan studi kasus. Data primer diperoleh dari wawancara dengan Petani Plasma Subsektor Perkebunan di Bengkulu, dan data sekunder diperoleh dari studi literatur yang bersumber dari buku, jurnal dan peraturan perundang-undangan. Penelitian ini menyimpulkan bahwa: (1). Kebijakan Kemitraan Orde Baru di Indonesia tidak dimaksudkan untuk melaksanakan prinsip usaha bersama dalam Pasal 33 UUD 1945, tetapi dalam rangka pelaksanaan proyek Bank Dunia dan IMF sejak tahun 1976, yang kemudian ditetapkan sebagai kebijakan investasi, pada tahun 1995; (2). Praktek kemitraan Inti-Plasma Subsektor Perkebunan pada masa Orde Baru menempatkan perusahaan Plasma di bawah Subordinasi Perusahaan Inti dan kurang memperoleh perlindungan dari Pemerintah, sehingga terjadi pola hubungan ekonomi yang eksploitatif; dan (3). Rekonstruksi Kebijakan Kemitraan Era Reformasi dilakukan dengan memberikan kemudahan perizinan berusaha, perlindungan hukum, dan pemberdayaan Koperasi, Usaha Mikro, dan Usaha Kecil, serta pemantauan kemitraan secara berkesinambungan.Kata-kata Kunci : Eksploitatif; era orde baru; era reformasi; kebijakan kemitraan; penenaman modal